J.K. Lasser's Guide to self-employment - Weltman, Barbara (John Wiley & Sons, 2014)
As a self-employed person you have to handle many, if not all, of the aspects of running your business. J.K. Lasser's Guide to Self-Employment is intended to help you with some business aspects with which you may not be familiar—but which have a great impact on your bottom line. It skillfully focuses on taxes as well as many legal and financial matters that may pertain to your business